(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
Thyroid hormones play an important role in regulating energy balance and metabolism of glucose and lipids. A relationship between dyslipidemia and atherosclerosis is well established in clinical hypothyroidism. Whether subclinical hypothyroidism (SCH) is associated with lipid profile alteration, is the main concept behind the study. SCH is defined as an elevated thyroid stimulating hormone (TSH>5mIU/l) and normal free thyroxine level (FT4 9.5- 25.0 pmol/l). It is highly prevalent in elderly subjects, especially in women but it is frequently overlooked. We examined 40 women with SCH and 50 healthy controls (TSH 0.5-5.0 mIU/l and FT4 9.5- 25.0 pmol/l). None of the patients had been previously treated with thyroxine. In all participants we measured blood pressure, BMI, TSH, FT4 and fasting serum lipid profile. We conclude that SCH in middle aged women is associated with hypertension and significant increase of TC (p<0.001), LDL-C (p<0.001), TG (p<0.001) and decreased level of HDLC p<0.001) in comparison to euthyroid Controls. SCH patients showed significant positive correlation between TSH and total cholesterol (r=.492, p<0.01), LDL-C (r=.355, p<0.05) and TG (r=.274, p<0.05) and negative but nonsignificant corelationship with HDL-C (r = - .058,p=0.361). Dyslipidemia is one of the established risk factors of cardiovascular diseases. Therefore, this study indicates that monitoring of lipid level in SCH patients would be helpful in preventing cardiovascular diseases. Bangladesh J Med Biochem 2015; 8(1): 10-15